Maintenance of autoantibody production in pristane-induced murine lupus. Issue 1 (December 2015) - Han, Shuhong; Zhuang, Haoyang; Xu, Yuan; Lee, Pui; Li, Yi; Wilson, Joseph; Vidal, Osvaldo; Choi, Hong; Sun, Yu; Yang, Li-Jun; Reeves, Westley
Abstract Background Pristane-treated mice chronically produce high levels of anti-ribonucleoprotein/Smith (anti-Sm/RNP) and other lupus autoantibodies. The present study addressed how these autoantibody levels are maintained over time. Methods Lupus was induced in BALB/c mice using pristane. Naïve B cells, switched memory B cells, switched plasmablasts, and plasma cells were flow-sorted and total IgG and anti-U1A (RNP) autoantibodies were determined with ELISA. Results B cells with a switched "memory-like" (CD19+ CD138− IgM− IgD− ) (sMB) phenotype were increased in pristane-treated mice and expressed higher levels of Toll like receptor 7 (Tlr7 ) than cells with this phenotype from untreated mice. Flow-sorted sMB cells from pristane-treated mice did not secrete IgG spontaneously, but were hyper-responsive to both synthetic (R848) and natural (apoptotic cells) TLR7 ligands, resulting in increased IgG productionin vitro . The flow-sorted sMB cells also could be driven by R848 to produce IgG anti-U1A autoantibodies. Production of IgG was strongly inhibited by both JSH-23 and SB203580, suggesting that the canonical NFκB and p38 MAPK pathways, respectively, contribute to the TLR7 ligand hyper-responsiveness of sMB from pristane-treated mice. Conclusions The switched memory B cell subset from pristane-treated mice is expanded and shows an increased propensity to undergo terminal (plasma cell) differentiation in response to synthetic and natural TLR7 ligands. The data suggest that the decreased clearance of apoptotic cells characteristic of pristane-treated mice might help maintain high serum levels of anti-RNP/Sm autoantibodies.